Representasi Korban dan Pelaku Kekerasan Seksual di Artikel Berita: Analisis Isi Artikel Berita detik.com Tahun 2021-2022 - Priyansyah, Rifki Nur; Sevira, Nada Indah; Rahmah, Siti Aulia; Pradipto, Aldo Dihardiko (Jurnal Pekommas, 2023)
The rape case of 14 female students drew public attention along with news highlighting the case a lot. Fifty-six detik.com news articles were collected using the eight constructed weeks sampling method which were analyzed using the quantitative content analysis to see the representations of perpetrators and victims of sexual violence and the changes that occurred between before and after the rape case emerged within one year (9 June 2021 to June 8, 2022). Coding was carried out by grouping articles into the age category of perpetrators and victims, gender of both, relationship between them, number of victims, repeated violence felt by victims, identity of perpetrators, and the time period. Based on the Chi-square test, for one year, reporting on sexual violence was dominated by victims who were children, single, women, and knew the perpetrators. Meanwhile, the perpetrators are predominantly male and middle-aged (if the victim is a child). Regarding period, news coverage of single victims with repeated violence has increased since the case emerged. Reporting that matches field data can provide awareness to the public, while victimization and monsterization need to be evaluated because they can affect public perception, which requires specific guidelines in reporting sexual violence cases.